Conception et validation d'un outil d'évaluation des besoins en matière de santé de la reproduction pour les femmes victimes de violence domestique - Mahrokh Dolatian; Abbas Ebadi; Seyedeh Batool Hasanpoor-Azghady; Anvar Sadat NayebiNia (BMC, 2022)
Plain English Summary Violence against women is a significant public health problem, as well as is a fundamental violation of women's human rights. Violence can negatively affect women's physical, mental, sexual and reproductive health. So there is obviously a need to measure this issue to provide necessary services for women experiencing violence. In current work an appropriate instrument was developed on the basis of the qualitative findings and a literature review. For this purpose, the inductive-deductive method was used to design the expressions and items of the tool. Both qualitative and quantitative methods were used to determine face and content validity. The construct validity was investigated by exploratory factor analysis; in this part of study the sample included three hundred and fifty violated women. The final version of the scale have four factors with total variance of 47.62 and 39 items which are evaluated by Likert scale. The current tool was valid and reliable to measure the reproductive health needs in domestic violated women.